The PAI-1 4G/5G polymorphism is not associated with an increased risk of adverse pregnancy outcome in asymptomatic nulliparous women - Said, J.; Tsui, R.; Borg, A.; Higgins, J.; Moses, Eric; Walker, S.; Monagle, P.; Brennecke, S. (2012)
Background: Plasminogen activator inhibitor type 1 (PAI-1) is an important regulator of fibrinolysis. A common deletion polymorphism that results in a sequence of 4G instead of 5G in the promoter region of the gene is associated with a small increase in the risk of venous thromboembolism. Its potential association with adverse pregnancy events remains controversial. Objective: We aimed to assess the impact of the 4G PAI-1 polymorphism on pregnancy outcomes in women who had no prior history of adverse pregnancy outcomes or personal or family history of venous thromboembolism. Patients/methods: This study represents a secondary investigation of a prior prospective cohort study investigating the association between inherited thrombophilias and adverse pregnancy events in Australian women. Healthy nulliparous women were recruited to this study prior to 22weeks gestation. Genotyping for the 4G/5G PAI-1 gene was performed using Taqman assays in an ABI prism 7700 Sequencer several years after the pregnancy was completed. Pregnancy outcome data were extracted from the medical record. The primary outcome was a composite comprising development of severe pre-eclampsia, fetal growth restriction, major placental abruption, stillbirth or neonatal death.Results: Pregnancy outcome data were available in 1733 women who were successfully genotyped for this polymorphism. The primary composite outcome was experienced by 139 women (8% of the cohort). Four hundred and fifty-nine women (26.5%) were homozygous for the 4G deletion polymorphism, while 890 (51.4%) were heterozygous. Neither homozygosity nor heterozygosity for the PAI-1 4G polymorphism was associated with the primary composite outcome (homozygous OR=1.30, 95% CI=0.81-2.09, P=0.28, heterozygous OR=0.84, 95% CI=0.53-1.31, P=0.44) or with the individual pregnancy complications. Conclusion: The PAI-1 4G polymorphism is not associated with an increase in the risk of serious adverse pregnancy events in asymptomatic nulliparous women.